Characteristics of chronic lymphocytic leukemia in Senegal. Issue 1 (December 2016) - Sall, Abibatou; Touré, Awa; Sall, Fatimata; Ndour, Moussa; Fall, Seynabou; Sène, Abdoulaye; Faye, Blaise; Seck, Moussa; Gadji, Macoura; Dièye, Tandakha; Mathiot, Claire; Reynaud, Sophie; et al.
Abstract Background Chronic lymphocytic leukemia (CLL) is a mature B-cell neoplasm characterized by the expansion of CD5-positive lymphocytes in peripheral blood. While CLL is the most common type of leukemia in Western populations, the disease is rare in Africans. Hence, clinical and laboratory data and studies of CLL in Sub Saharan populations have been limited. The aims of this study were to analyze the characteristics of senegalese patients with CLL at the time of the diagnosis and to identify the correlation between clinical characteristics (Binet stage) with age, gender, laboratory parameters and chromosomal abnormalities. Methods In this study, we investigated the clinical and laboratory characteristics of CLL in Senegal. A total of 40 patients who had been diagnosed with CLL during the period from July 2011 to April 2015 in Senegal were evaluated. Cytology and immunophenotype were performed in all patients to confirm the diagnosis. The prognosis factors such as Binet staging, CD38 and cytogenetic abnormalities were studied. The statistical analysis was performed using STATA version 13 (Stata college station Texas). Each patient signed a free and informed consent form before participating in the study. Results The mean age was 61 years ranged from 48 to 85. There were 31 males and only 9 females (sex ratio M : F = 3, 44). At diagnosic, 82.5 % of the patients were classified as having advanced Binet stages B or C. The prognosis marker CD38 was positive in 28 patients. Cytogenetic abnormalities studied by FISH were performed in 25 patients, among them, 68 % (17 cases) had at least one cytogenetic abnormality and 28 % had 2 simultaneous cytogenetic abnormalities. Conclusion Africans may present with CLL at a younger age and our data suggest that CLL in Senegal may be more aggressive than in Western populations.